The Impact of Leadership Styles on Organizational Agility and Success - Reddy, Dhivya (Digital Repository of Theses - SSBM Geneva, 2024)
This research investigates the impact of three leadership styles—transformational, transactional, and laissez-faire—on organizational agility and success. The study aims to determine which leadership style most effectively enhances an organization’s ability to adapt and thrive in dynamic environments. The research employed a quantitative approach, collecting data from 300 respondents across various organizations. A series of statistical tests, including Confirmatory Factor Analysis, Principal Component Analysis, and Structural Equation Modeling, were conducted to validate the relationships between leadership styles, organizational agility, and success. The study also assessed the reliability and validity of the constructs used in the analysis. Results revealed that transformational leadership significantly enhances both organizational agility and success. Respondents generally perceived this leadership style vi positively, with high communalities and factor loadings supporting its influence on the desired outcomes. Transactional leadership also positively impacted agility and success, though to a lesser extent. Laissez-faire leadership, while positively perceived, showed a weaker direct effect on organizational success and a negative impact on organizational agility. Furthermore, the study found that organizational agility partially mediates the relationship between transformational and transactional leadership styles and organizational success. This suggests that while these leadership styles directly contribute to success, their impact is amplified when they also enhance organizational agility. In contrast, laissez-faire leadership’s negative effect on agility detracts from its overall impact on organizational success. In conclusion, the research underscores the importance of transformational and transactional leadership styles in fostering organizational agility and success. Organizations are advised to prioritize these leadership approaches to enhance their adaptability and performance. The findings also indicate the need for further exploration into the effects of laissez-faire leadership and other potential moderating factors that may influence the relationship between leadership styles and organizational outcomes. This study provides valuable insights for both academic researchers and organizational leaders seeking to optimize leadership strategies for improved agility and success.